PERUBAHAN MODEL MANAJEMEN KARIER : A THEORETICAL REVIEW - Putra, Yanuar Surya (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2009)
Human Resources Divison have a very important role in an Organization, especially in designing a career path and improving the quality of all Human Resources in Organization, in other words Human Resources peoples have to create a career management process to all employees. According to Kanter ( 1995 ) the evolving and changes in economic and business world cause a greater continuing job dislocation, insecurity, and job requirement, that also will lead into changes in employees world. So the important of Career Management should be considerable to all Human Resources peoples. This article will discuss about management career models that suitable with global changes and how employees can develop their career path to gain a better future. Keywords : Management Career Model, Human Resources Management